2015
DOI: 10.1002/mrm.25597
|View full text |Cite
|
Sign up to set email alerts
|

Super‐resolution reconstruction of diffusion parameters from diffusion‐weighted images with different slice orientations

Abstract: Purpose: Diffusion MRI is hampered by long acquisition times, low spatial resolution, and a low signal-to-noise ratio. Recently, methods have been proposed to improve the tradeoff between spatial resolution, signal-to-noise ratio, and acquisition time of diffusion-weighted images via super-resolution reconstruction (SRR) techniques. However, during the reconstruction, these SRR methods neglect the q-space relation between the different diffusion-weighted images. Method: An SRR method that includes a diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…The quadratic term in (8) corresponds to the assumption that the noise components in Y k 's follow Gaussian distributions which is usually assumed in SRR methods, see e.g. [17, 21]. For other type of distributions, such as Rician distribution, the quadratic term can be replaced by the corresponding log-likelihood functions as was done in [50].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The quadratic term in (8) corresponds to the assumption that the noise components in Y k 's follow Gaussian distributions which is usually assumed in SRR methods, see e.g. [17, 21]. For other type of distributions, such as Rician distribution, the quadratic term can be replaced by the corresponding log-likelihood functions as was done in [50].…”
Section: Methodsmentioning
confidence: 99%
“…For other type of distributions, such as Rician distribution, the quadratic term can be replaced by the corresponding log-likelihood functions as was done in [50]. However, the Gaussian assumption is valid for high SNR (SNR>5) [21, 51]. Moreover, using a quadratic term in (8) usually leads to computationally efficient algorithms which is preferred in solving large scale optimization problems.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, these methods require the same number of measurements (e.g., 60 gradient directions) for each LR acquisition. To address this problem, more recently, [8] introduced a method that used the diffusion tensor imaging (DTI) technique to model the diffusion signal in q-space. However, a very simplistic diffusion tensor model was assumed, which is not appropriate for modeling more complex diffusion phenomena (crossing fibers).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, precise and accurate high resolution T 1 mapping is infeasible in clinical practice. Recent work has shown that super-resolution (SR) reconstruction methods can provide MR images with an improved trade-off between acquisition time, SNR and spatial resolution [12][13][14][15], by reconstructing an isotropic high resolution image from a set of images with a high in-plane and low through-plane resolution.…”
Section: Introductionmentioning
confidence: 99%